"I'm not proud, I'm just gay": lesbian and gay youths' discursive negotiation of otherness - Jones, Lucy (Wiley, 2018)
This article outlines the shared identity construction of five gay and lesbian members of an LGBT youth group, situated in a conservative, working-class, Northern English town. It is shown that the young people’s identity work emerges in response to the homophobia and ‘othering’ they have experienced from those in their local community. Through ethnography and discourse analysis, and using theoretical frameworks from interactional sociolinguistics, the strategies that the young people employ to negotiate this othering are explored; they reject certain stereotypes of queer culture (such as Gay Pride or being ‘camp’), and aim to minimise the relevance of their sexuality to their social identity. It is argued this reflects both the influence of neoliberal, ‘homonormative’ ideology, which casts sexuality in the private rather than public domain, and the stigma their sexuality holds in their local community. These findings point to the need to understand identity construction intersectionally.